BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU HAMIL MENGENALI TANDA BAHAYA PREEKLAMSIA KEHAMILAN - Gustini, Gustini; Arini, Arini; Musaidah, Musaidah; Indrani4, Farihah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: WHO estimates that preeclampsia cases are seven times higher in developing countries than in developed countries. The purpose of this study was to determine several factors associated with the knowledge of pregnant women to recognize the danger signs of pregnancy preeclampsia. The research design used in this study was cross sectional. The research was conducted in the working area of Kuwarasan Health Center. The research was conducted in August 2024. The study population was all maternity mothers registered at the health center. The sample amounted to 83 respondents. The sampling technique used Simple random sampling. Data analysis was performed univariate and bivariate using the SPSS program. The results showed a relationship between education (p value: 0.038) and information exposure (p value: 0.049) to the level of maternal knowledge. It is recommended for puskesmas to increase the prenatal class program for pregnant women routinely, provide health education, especially how to overcome or prevent the incidence of preeclampsia.Keywords: Information Exposure, Preeclampsia, Education.